Decolonizing Resistance, Challenging Colonial States - Sharma, Nandita (Social justice, 2008)
A commentary on an article by Bonita Lawrence and Enakshi Dua that appeared in Social Justice, vol. 32, no. 4, 2005, pp. 120–143. Lawrence and Dua asserted that antiracist theory and practices have historically excluded the concerns of Aboriginal people and contributed to their active colonization. The writers challenge the conflation between processes of migration and those of colonialism and interrogate the claim that decolonization may be achieved through the nationalist project. They conclude with a consideration of ways to bridge the divide between indigenous people and migrants by working toward practices of decolonization that are antiracist.